2021
DOI: 10.3390/microorganisms10010070
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution and Transmission of Gut Microbiomes and Their Genes between Generations

Abstract: Microbiomes are transmitted between generations by a variety of different vertical and/or horizontal modes, including vegetative reproduction (vertical), via female germ cells (vertical), coprophagy and regurgitation (vertical and horizontal), physical contact starting at birth (vertical and horizontal), breast-feeding (vertical), and via the environment (horizontal). Analyses of vertical transmission can result in false negatives (failure to detect rare microbes) and false positives (strain variants). In huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 286 publications
(257 reference statements)
0
19
0
2
Order By: Relevance
“…The study of phages within a single primate species, baboons, revealed that neighboring social groups harbored evolutionarily and compositionally distinct phageomes that were structured by their superhost’s social behavior; close grooming partners had more similar phage communities, even after controlling for relatedness or diet of the superhosts [ 16 ]. This study joined a growing body of literature suggesting that maintenance of microbial communities within groups through social behavior serves to create a pan-microbiome that can act to maintain microbial diversity across evolutionary time scales and contributing to the evolution of host species-specific gut microbial communities [ 18 , 19 ].…”
Section: First Insights Into the Origins Of The Human Phageomementioning
confidence: 89%
“…The study of phages within a single primate species, baboons, revealed that neighboring social groups harbored evolutionarily and compositionally distinct phageomes that were structured by their superhost’s social behavior; close grooming partners had more similar phage communities, even after controlling for relatedness or diet of the superhosts [ 16 ]. This study joined a growing body of literature suggesting that maintenance of microbial communities within groups through social behavior serves to create a pan-microbiome that can act to maintain microbial diversity across evolutionary time scales and contributing to the evolution of host species-specific gut microbial communities [ 18 , 19 ].…”
Section: First Insights Into the Origins Of The Human Phageomementioning
confidence: 89%
“…Bacteria such as Parabacteroides distasonis, Alistipes onderdonkii, Bacteroides faecis, Bacteroides caccae and Bacteroides salyersiae from the maternal oral cavity and skin are frequently transferred to infants through kissing, touching and hugging. [208][209][210] One study focused on early microbial seeding and suggested that fathers also play an essential role in the establishment of the neonatal microbiome. 8 Distinct from maternal seeding at the start of birth, fathers mainly provide novel strains that colonise infants later in life.…”
Section: Contact and Other Sourcesmentioning
confidence: 99%
“…The extensive range of variability in the bacteriome of helminths leads to questioning the microbial sources of individual helminths in a population (Rosenberg & Zilber-Rosenberg, 2021): helminths may horizontally acquire bacteria, from their habitat, be it the external environment when they are in the infectious larval stages, or their surroundings within their host, and their diet, whatever they feed on (host tissue, or even other co-infecting parasites) (Jorge et al, 2020(Jorge et al, , 2022b. Helminths may also vertically acquire bacteria, which means bacteria are transmitted among parasite generations (Jorge et al, 2020(Jorge et al, , 2022b.…”
Section: Introductionmentioning
confidence: 99%